Toleransi Beberapa Klon Karet (Hevea brasiliensis Muell. Arg.) pada Media Tailing Pasir Pasca Tambang Timah - Inonu, Ismed; Budianta, D; Umar, M; Wiralaga, AYA (Universitas Bangka Belitung, 2010)
The objective of this study was to evaluate the tolerance of the six combinations of the recommended rubber clones in the tin post-mining tin sand s media . The experiment conducted in Reclamation Nursery of PT Koba Tin Sub District of Koba District of Central Bangka during 4 month. This experiment was designed according to completely randomized design. The Treatment factor is a combination of rootstock and scion clones, consisting of (GT 1 + BPM 24), (GT 1 + PB 260), (1 + IRR GT 118), (PB 260 + BPM 24), (PB 260 + PB 260), and (PB 260 + IRR 118). Each treatment consisted of three replications and each replication consisted of three plants. The rubber tree seedlings are planted on mixing of s sand, top soil and manure chicken manure (2:1:2, v/v), and on non-mining land media as a control. The variables are percentage of seedling, shoot length, shoot diameter, number of leaf petiole, leaf area, shoot biomass, root biomass, total biomass, specific leaf area ratio and root shoot ratio was measured at 20 MST. Data were analyzed statistically with analysis of variance and Duncan multiple range test. The growth of rubber seedlings on sand s media were ameliorated with top soil and chicken manure was lower than in non-mining soil media. Based on the results of tolerance tests,of six combinations of clones, the combination of GT 1 clone as rootstock and clone PB 260 as entres was classified quite tolerant category and produce better growth than the other clones.